2012
DOI: 10.1093/jxb/ers026
|View full text |Cite
|
Sign up to set email alerts
|

Fruit-specific RNAi-mediated suppression of SlNCED1 increases both lycopene and β-carotene contents in tomato fruit

Abstract: Abscisic acid (ABA) plays important roles during tomato fruit ripening. To study the regulation of carotenoid biosynthesis by ABA, the SlNCED1 gene encoding 9-cis-epoxycarotenoid dioxygenase (NCED), a key enzyme in the ABA biosynthesis, was suppressed in tomato plants by transformation with an RNA interference (RNAi) construct driven by a fruit-specific E8 promoter. ABA accumulation and SlNCED1 transcript levels in the transgenic fruit were down-regulated to between 20–50% of that in control fruit. This signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(102 citation statements)
references
References 46 publications
11
90
0
1
Order By: Relevance
“…The expression of ACS2, ACS4, and ACO1 genes is induced by exogenous ABA, revealing an ABA/ ethylene interplay operating at the level of ethylene biosynthesis (Chernys and Zeevaart, 2000;Jiang et al, 2000;Zhang et al, 2009). Down-regulation of the key ABA biosynthesis enzyme 9-cis-epoxycarotenoid dioxygenase1 in tomato fruit resulted in altered firmness and color but surprisingly higher ethylene production, indicating the complexity of the ABA/ethylene interplay during ripening (Sun et al, 2012). In tomato, ABA might also be perceived through an ethylene-independent pathway that is mediated by tomato Zinc Finger Transcription Factor (Weng et al, 2015).…”
Section: Ethylene and Other Phytohormones In Fruit Ripeningmentioning
confidence: 99%
“…The expression of ACS2, ACS4, and ACO1 genes is induced by exogenous ABA, revealing an ABA/ ethylene interplay operating at the level of ethylene biosynthesis (Chernys and Zeevaart, 2000;Jiang et al, 2000;Zhang et al, 2009). Down-regulation of the key ABA biosynthesis enzyme 9-cis-epoxycarotenoid dioxygenase1 in tomato fruit resulted in altered firmness and color but surprisingly higher ethylene production, indicating the complexity of the ABA/ethylene interplay during ripening (Sun et al, 2012). In tomato, ABA might also be perceived through an ethylene-independent pathway that is mediated by tomato Zinc Finger Transcription Factor (Weng et al, 2015).…”
Section: Ethylene and Other Phytohormones In Fruit Ripeningmentioning
confidence: 99%
“…Besides ethylene and the abovementioned regulators, ABA also is implicated to play a role in the fruit ripening of tomato and other species, including nonclimacteric fruit crops such as strawberry (Fragaria ananassa) and grape (Vitis vinifera; Jia et al, 2011;Seymour et al, 2013), although the mechanism remains unclear. In tomato, repression of LeNCED1 decreases the expression of several genes encoding ripening-associated cell wall enzymes and delays fruit ripening, suggesting that ABA promotes ripening (Sun et al, 2012b).…”
Section: Supersensitive To Abscisic Acid and Drought1mentioning
confidence: 99%
“…Clade A PP2Cs function as negative regulators of the ABA signalling pathway and their transcript levels are highly induced by ABA in plants (Merlot et al, 2001;Saez et al, 2004;Saez et al, 2006;Yoshida et al, 2006b;Xue et al, 2008;Li et al, 2009) Fig.1 and 4A, Results Chapter 1), which agreed with results reported in harvested grapes and tomatoes (Sun et al, 2010;Sun et al, 2012a;Sun et al, 2012b) and in vegetative tissues (Tan et al, 2003;Loyola et al, 2012;Frey et al, 2012). Interestingly, CsNCED1 followed an expression pattern highly similar to that displayed by the members of the CsPP2CA family in citrus fruit (Fig.2, Results Chapter 3).…”
Section: Discussionsupporting
confidence: 79%
“…Studies performed in tomato, avocado, peach and persimmon indicated that NCED genes expression was induced as ripening progressed, showing a maximum before the ethylene production (Chernys and Zeevaart, 2000;Leng et al, 2009;Zhang et al, 2009a;Sun et al, 2012b). In nonclimacteric fruits such as strawberry, watermelon, sweet cherry and grape, NCED genes were mainly induced in response to water stress and ABA application, and transcripts accumulation paralleled ABA increase during fruit ripening (Zhang et al, 2009a;Ren et al, 2010;Ji et al, 2012;Li et al, 2012b).…”
Section: Regulation Of Aba Levelsmentioning
confidence: 99%